Prediction of preterm labour by cervical length - Wadhawan, Urvi Tanna; Shah, Neelima P.; Patil, Ajit N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm birth is one of the commonest causes of perinatal mortality. Cervical length is one of the major determinants of preterm delivery. Methods: This prospective observational study of 100 pregnant women attending ANC OPD was carried out at D.Y. Patil Hospital, Kolhapur. The pregnant women were scanned for cervical length between 11-14 weeks and 20-22 weeks of gestation, using USG machine with TVS probe (mindray DC-7). Results: The mean value of cervical length in pregnant women at 11-14 weeks was 3.94 cm and at 20-22 weeks of gestation it was 3.38 cm. There was shortening in the pregnant cervix from first to second trimester. In the study 12% of patients delivered prematurely who had reduction in cervical length from first trimester to second trimester. The inverse relation between the cervical length during pregnancy and frequency of preterm delivery was confirmed. The decrease in cervical length at 11-14 weeks of gestation and 20-22 weeks of gestation was useful for identifying patients at increased risk for pre-trerm. Conclusions: Our findings confirm those of previous studies that have found an inverse relation between the length of the cervix, as measured by transvaginal ultrasonography during pregnancy, and the frequency of preterm delivery. We found that the cervical length measured at 11-14 weeks and 20-22 weeks gestation was decreased in asymptomatic women with single to n pregnancies was useful for identifying patients at increased risk for preterm delivery.